(3cTa GdQhGb Yf UQa GdLGeYI ddChQGbs - (3CHh GdYHGS Hf CMeOs
(3ChdgG (B:s
(3hHYO acKjQkG eG cGf jJadJ Ydjg ai Yed dCFeI GdChajI s
(3BNQgG (B:s
(3hEf NGda HYV GdCFeI GdChajI s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3eUOQ GbJfGA GdCUd (B:s
(3GdeZQH ecJHI GdQHGW (B(D 493) s
Keywords: (3Yde GdaQGFVs